9 tips to improve your wellbeing and quality of life - Abdullah, Nasiha (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
If you are a person who remains busy in work and other matters and pays little attention to your health and wellbeing, you must take a break from the robotic routine and adopt healthy habits. According to a psychologist, eating well and exercising provide immediate advantages to your body and brain in terms of stress, depression, and anxiety management. True happiness derives from a state of balance, ongoing progress, and acceptance.